Penerapan Model Talking Stick untuk Meningkatkan Hasil Belajar pada Materi Matematika Satuan Waktu di Kelas III MI Cibuntu - Nurkaidah Nurkaidah; Dwi Kartika Susanti (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Mathematics is an important science. Therefore mathematics needs to be applied early on in children. before the research, in adding hours, minutes and seconds in Grade III MI Cibuntu using the equivalence technique of hours, minutes and seconds. It turned out that after this technique was implemented in grade III, the learning outcomes achieved by students were always unsatisfactory with an average evaluation result of only reaching 57, and some students actually experienced difficulties with obtaining scores far below the KKM mathematics score that had been set, namely 65. The problem Another thing that arises is the length of time to complete. For this reason, a research was conducted entitled "Application of the talking stick model to improve learning outcomes in mathematics material (Time Unit) in grade III MI Cibuntu, Cicurug sub-district. This type of research was classroom action research using the talking stick model. Each cycle consists of four stages, namely Planning, Implementation, Observation and Reflection. As research subjects are grade III students of MI Cibuntu. Data collection techniques using observation, written tests,. From the research results, it was found that student activity increased in each cycle, namely active students asking questions increased 25%, accuracy in using the talking stick base increased 20.2%, and accuracy increased 23.75%. While the learning outcomes are an increase in the average value of Mathematics learning outcomes obtained by students from before. In the first cycle the percentage of student completeness was 66.67% then in the second cycle it became 100%. Based on the results of the research above, it can be concluded that learning mathematics using a talking stick basis can improve the skills of adding up units of time in third grade students of MI Cibuntu. Keywords: Improvement, Learning Outcomes, Talking stick basis